Memory is movement - Nin, Alice (GIS - Gesture, Image and Sound - Anthropology Journal, 2021)
The photo essay Memory is movement is about the encounter with personal archive photographs of residents of Azul, in Jacarezinho (Rio de Janeiro), gathered by the exhibition Outro Olhar, conceived by the collectives Cafuné na Laje and Norte Comum. Having the exhibition’s research process as a starting point, the photographs focus on the importance of mobilizing visual memory of personal archives. The aim was to approach and share these portal-images and promote a way of perceiving and experiencing photography collectively, while strengthening community bonds. The emphasis was placed on the historical importance of the territory from within, of how it is visually signified. Thus, the recognizing and valuing of these archives is a necessity for the contemporary debate about photographic images and their participation in the construction of a territory’s collective memory.